Intensive use of energy resources regarding sustainable cities; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Matyugina E. G. Eleonora Grigorievna; Pozharnitskaya O. V. Olga Vyacheslavovna; Petrova K. O.; Strelnikova A. B. Anna Borisovna (Petroleum Engineering Economics. Mining Law, 2015)
Title screen